Granting maternity pay to indigenous women: the Guarani case (Revista do Tribunal Regional Federal da 3ª Região, 2020)
The article raises possible social, economic, cultural and budgetary impacts of granting or not the maternity wage to indigenous women under the age of 16 (sixteen) of the Guarani ethnic group in collective actions. The work uses the outlines of Public Civil Action nº 5009160-45.2018.4.03.6100 to make the reader aware of hypothetical effects arising from the judicialization of this social security issue.
Keywords: maternity pay; consequentialism; judicialization